2021
DOI: 10.1186/s40479-021-00149-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbid borderline personality disorder on the outcome of inpatient treatment for anorexia nervosa: a retrospective chart review

Abstract: Background Data on patients with anorexia nervosa (AN) and comorbid Borderline personality disorder (AN+BPD) are scarce. Therefore, we investigated (1) whether patients with AN and AN+BPD differ in characteristics related to admission to, discharge from, and course of specialized inpatient eating disorder treatment and (2) how comorbid BPD affects treatment outcome. Method One-thousand one-hundred and sixty inpatients with AN (97.2% female, 5.9% wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
(16 reference statements)
2
8
0
Order By: Relevance
“…However, the presence of PD, particularly AvPD, was found to moderate premature attrition in anorexia nervosa (Jordan et al, 2014), which in turn has been linked to poorer long‐term prognosis (Fassino et al, 2009; Kahn & Pike, 2001; Vall & Wade, 2015), a higher likelihood of relapse and future re‐referral to specialist centres (Halmi et al, 2005; Strober et al, 1997). These findings are consistent with previous studies that report personality factors as predictive of higher attrition in the ED population (Fassino et al, 2009; Nozaki et al, 2007; Pham‐Scottez, 2015; Pham‐Scottez et al, 2012; Voderholzer et al, 2021). Avoidant personality traits in particular have been shown to predate the onset of anorexia nervosa and to persist even following weight restoration, limiting quality of life and increasing risk of relapse, indicating that they may function as both risk and maintaining factors in this population (Casper, 1990; Schmidt & Treasure, 2006; Troop & Treasure, 1997; Troop et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the presence of PD, particularly AvPD, was found to moderate premature attrition in anorexia nervosa (Jordan et al, 2014), which in turn has been linked to poorer long‐term prognosis (Fassino et al, 2009; Kahn & Pike, 2001; Vall & Wade, 2015), a higher likelihood of relapse and future re‐referral to specialist centres (Halmi et al, 2005; Strober et al, 1997). These findings are consistent with previous studies that report personality factors as predictive of higher attrition in the ED population (Fassino et al, 2009; Nozaki et al, 2007; Pham‐Scottez, 2015; Pham‐Scottez et al, 2012; Voderholzer et al, 2021). Avoidant personality traits in particular have been shown to predate the onset of anorexia nervosa and to persist even following weight restoration, limiting quality of life and increasing risk of relapse, indicating that they may function as both risk and maintaining factors in this population (Casper, 1990; Schmidt & Treasure, 2006; Troop & Treasure, 1997; Troop et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with large open naturalistic trials conducted across both inpatient and outpatient settings, which have found that those with co-morbid PD tend to be associated with a higher number of inpatient admissions, longer length of admission and a higher likelihood of being rated as unfit to work at discharge compared with those without co-morbidity (Hessler et al, 2019;Zeeck et al, 2007). Similarly, although no RCTs were identified which examined the effect of PD co-morbidity on treatment outcomes in anorexia nervosa, a large recent open trial of inpatients with anorexia nervosa found similar outcomes to those reported for bulimia nervosa with co-morbid PD, with reduced treatment responses in relation to general psychopathology, impulse regulation, perfectionism and body dissatisfaction, highlighting the need for future studies to investigate this area (Voderholzer et al, 2021).…”
Section: Treatment Effects Of Pd On Ed Outcomesmentioning
confidence: 98%
“…interpersonal difficulties, unstable self-image and self-esteem, marked impulsivity, dysfunctional defense mechanisms, and emotion dysregulation might play a relevant role in determining response to ED treatment (Martinussen et al, 2017;Voderholzer et al, 2021). In line with previous empirical evidence, cooccurring Cluster B symptoms in an ED patient may mark greater severity, and thus potentially predict a poorer outcome and less symptomatic change (Steiger et al, 1993;Hessler et al, 2019).…”
Section: Discussionsupporting
confidence: 57%
“…ED patients with comorbid personality pathology have been found to present more severe overall psychopathology (according to anxiety, depression, somatization, psychoticism, and global severity scales) (e.g., Wonderlich et al, 1994) and higher levels of ED symptoms (Westen and Harnden-Fischer, 2001;Hopwood et al, 2010). More specifically, some outcome studies have found borderline personality disorder comorbidity and other Cluster B personality traits to predict negative therapy outcomes (Fahy et al, 1993;Rossiter et al, 1993;Voderholzer et al, 2021). Furthermore, follow-up studies with mixed ED samples have shown that baseline borderline symptoms relate to lower overall functioning, higher levels of ED symptoms, and lower rates of therapeutic change and life satisfaction (Sansone and Fine, 1992;Wonderlich et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, comorbid PDs in AN are associated with worse outcomes, e.g., elevated mortality (17). Comorbid Borderline PD in AN was associated with fewer treatment-related improvements of global functioning and body dissatisfaction (18). Moreover, comorbid PDs were associated with more frequent treatment drop out and less weight gain specifically in young adult AN patients aged 17-24 (19).…”
Section: Introductionmentioning
confidence: 99%